Consumer Protection in Illegal Online Lending Practices: A Private Law Analysis and Enforcement Efforts - Ratih Agustin Wulandari; Toni Nieta; Ahmad Taufik (Journal of Innovative and Creativity, 2025)
This research critically examines consumer protection within the context of illegal online lending practices in Indonesia, analyzed through the lens of private law. The proliferation of unauthorized online lending platforms has exposed individuals to severe financial and psychological harm due to exorbitant interest rates, hidden fees, and coercive collection methods, highlighting a pressing need for robust legal safeguards. Employing a normative legal research methodology, this study primarily analyzes relevant statutes, legal doctrines, and case law pertaining to contract law, consumer protection, and torts. It identifies the inherent violations of private law principles by illegal lenders and scrutinizes the effectiveness of existing legal remedies and enforcement efforts by regulatory bodies and law enforcement. The findings reveal persistent challenges in applying current legal frameworks to the complex nature of illegal online lending, emphasizing the need for clearer legal interpretations, enhanced inter-agency coordination, and strengthened mechanisms for data protection and digital evidence. This study aims to contribute to legal scholarship and inform policy recommendations for more effective consumer protection against illicit online lending activities.